Neuropeptide Control of Puberty: Beyond Kisspeptins - Barroso, Alexia; Roa, Juan; Tena-Sempere, Manuel (Seminars in Reproductive Medicine, 2019)
Puberty is a fundamental developmental event in the lifespan of any individual, when sexual and somatic maturation is completed, and reproductive capacity is achieved. While the tempo of puberty is under strong genetic determination, it is also modulated by a wide array of internal and environmental cues, including, prominently, nutritional and metabolic signals. In the last decade, our understanding of the neurohormonal basis of normal puberty and its perturbations has enlarged considerably. This is illustrated by the elucidation of the essential roles of kisspeptins, encoded by the Kiss1 gene, in the hypothalamic circuits controlling puberty. Moreover, other neuropeptide pathways, convergent with kisspeptin signaling, have been pointed out as important coregulators of pubertal timing. These include the cotransmitters of Kiss1 neurons in the arcuate nucleus (ARC), neurokinin B, and dynorphin, as well as melanocortins, produced by ARC neurons expressing proopiomelanocortin, which are endowed with key roles also in the control of metabolic homeostasis. This neuropeptide setup seemingly participates, in a coordinated manner, in transmitting the regulatory actions of metabolic cues on pubertal maturation. In this function, cellular metabolic sensors, such as the AMP-activated protein kinase, and the fuel-sensing deacetylase, SIRT1, have also been shown recently to contribute to the metabolic regulation of puberty. Altogether, elucidation of the physiological roles of these signals and regulatory circuits will help uncover the intimacies of the brain control of puberty, and its alterations in conditions of metabolic stress, ranging from subnutrition to obesity.
Keywords: puberty; kiss1; kisspeptins; GnRH; NKB; dynorphin; KNDy; melanocortins; obesity